A Study of the Non-Visual Factors of Cars Affecting the Consumer’s Cognitive Appeal - Jitender Singh; Parth Ahuja; Prabir Sarkar (Journal of Visual Art and Design, 2022)
The success of a car in the market depends on visual as well as non-visual factors. Both these sets of factors influence the cognitive appeal of cars for potential buyers. Purchasing a car is not only about economic choices but also related to emotional, aesthetic, sensory responses to driving, kinship patterns, habitation, sociability, and functionality. This study aimed to identify the major non-visual factors of cars that affect the cognitive perception of buyers and estimate their importance relative to each other. A set of non-visual factors and their sub-factors were identified through a literature search and an open-ended survey among car owners. Many of the sub-factors had the same meaning and therefore these factors were grouped under twenty separate sub-factors. Then, these twenty sub-factors were analyzed by using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) approach to evaluate the most influential sub-factors among the identified sub-factors. Six designers were involved in the analysis of the sub-factors through the DEMATEL approach. The results showed that the car’s brand value, cost, engine performance, reliability, and safety are the top five sub-factors. Outcomes of this study can be utilized by designers and top management people to understand the most influential factors affecting the cognitive behavior of consumers when purchasing a car. This understanding will help companies to design cars as per the requirements of consumers, which will ultimately lead to better profitability of these companies.